(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Our research team developed a Faculty Information System (FIS, profiling). This system is being used to manage teachers’ data and information. Our was Bestlink College of the Philippines. We found that Bestlink College of the Philippines does not have an existing FIS and only uses folders and Microsoft Excel in storing and managing teachers’ data. Bestlink College of the Philippines also encountered several problems in managing data such as searching teachers’ data that are stored in folders, which is time-consuming and also has an extremely high risk of data security. Hence, we built a system that can solve all problems Bestlink College of the Philippines encountered. The method used was the system development life cycle, which has seven phases, namely, planning, analysis, design, development, testing, implementation, and maintenance. During the planning phase, we proposed a project budget proposal and prepared a feasibility study. We gathered all the data we needed by interviewing the proponents and observing the current system. From the data gathered, we made a blueprint for our system based on what our client requested using design tools such as UML. After developing the system, we tested all its features and implemented it after ensuring that is it free from errors. The demonstration of the system functions and how it works was provided to the client for familiarity purposes. As we tested our system including all its functions and features, such as audit trail, login attempts, searching, deleting, updating, editing, and adding profile features, it successfully met the client’s requirements. Searching the teachers’ data became easy, and Bestlink College of the Philippines now has a better security feature because our system contains an audit trail that can record the system’s user time-in and time-out. Our system has also an interface for user log-in that requires a username and password to access the system. The primary purpose of this study was to make a system that is secured, simple, easy to use, and can provide a better FIS for Bestlink College of The Philippines. Based on our study of published articles about FIS, each one of the FIS in every school has unique and extremely useful features, but they have similar features such as high security in every data and information being stored in the system. Our system complied with these features because it has a Faculty Profile that can easily be accessed by system users by providing a searching feature by using the Employee ID. Our system also has delete, update, and add features.